Las categorías de la conquista: las mujeres nativas en el vocabulario del siglo XVI (São Vicente, Brasil) - Elisa Frühauf Garcia (Nuevo mundo - Mundos Nuevos, 2019)
The participation of native women was crucial for Portuguese colonization in their first settlements in mid-sixteenth century Brazil. In fact, the term “índia” (an Indian woman) was rarely used by contemporaries. In the historical documents from that time other categories were employed, such as “negra” (black woman), “peça” (piece), “criada” (servant), “escrava” (slave), “fêmea” (female), “mestiça”, and “mameluca” (both used for women of mixed Portuguese and Indian ancestry). Starting with these terms, this article aims to analyze the presence of Tupi-Guarani women in the process of the formation of colonial society, more particularly in the Captaincy of São Vicente. In order to do so, the role of these women in the commercial and diplomatic relationships between native leaders and the Portuguese will be examined, as well as their insertion in the incipient social hierarchies triggered by the conquest.